EXPLORING ETHNOMATEMATICS IN TRADITIONAL GETUKAND KUE LAPIS FOODS FROM JAVA AS A SOURCE OF MATHEMATICAL LEARNING - Harahap, Ananda Aditya Sari; Ananda, Rusydi (JME (Journal of Mathematics Education), 2025)
Mathematics is often regarded as an abstract and formal discipline, which can create a disconnect between students’ understanding and real-worldapplications. Ethnomathematics offers a culturally responsive approach by uncovering mathematical practices embedded in local traditions, thereby making mathematics learning more contextual and meaningful. This study aims to explore the ethnomathematical elements found in traditional Javanese foods getuk and kue lapis and analyze their potential as culturally grounded resources for mathematics instruction. Employing a qualitative approach with ethnographic methods, the research was conducted in a Javanese community in North Sumatra, involving traditional food makers as key informants. Data were collected through direct observation, semi-structured interviews, and documentation. The analysis revealed the presence of mathematical concepts such as geometric shapes, proportional reasoning, repeated patterns, and symmetry in food preparation and presentation. These findings suggest that traditional food-making processes can serve as contextual media for teaching geometry and proportional concepts at the primary and secondary school levels. Integrating such ethnomathematical elements into instructional materials not only enhances conceptual understanding but also fosters cultural awareness and appreciation. Therefore, this study highlights the relevance of local cultural practices as an innovative foundation for the development ofculturally contextualized mathematics education.